Рівняння ПЖ (x ^ 2-1) (x ^ 2 + 3) = (X ^ 2 + 1) ^ 2 + x

Рівняння ПЖ (x ^ 2-1) (x ^ 2 + 3) = (X ^ 2 + 1) ^ 2 + x

  • ви ввели
    2
    / 2/2/2
    x - 1 / * x + 3 / = x + 1 / + x
    відповідь
    x1 = -4
  • (X ^ 2-1) (x ^ 2 + 3) = (X ^ 2 + 1) ^ 2 + x
    x ^ 4-x ^ 2 + 3x ^ 2-3 = x ^ 4 + 2x ^ 2 + 1 + x
    x ^ 4-x ^ 2 + 3x ^ 2-3-x ^ 4-2x ^ 2-1-x = 0
    -x-3-1 = 0
    -x-4 = 0
    -x = 4
    x = -4
Понравилась статья? Поделиться с друзьями:
Добавить комментарий

+ 43 = 47

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!: